Alternatives to Autopsy for Fetal and Early Neonatal (Perinatal) Deaths: Insights from the Wisconsin Stillbirth Service Program. Issue 18 (12th September 2017) - McPherson, Elspeth; Nestoridi, Eirini; Heinke, Dominique; Roberts, Drucilla J.; Fretts, Ruth; Yazdy, Mahsa M.; Lin, Angela E.
Abstract : Background: Although autopsy is a key component of the etiologic evaluation following fetal and early neonatal death, and traditionally has been the preferred method to determine the cause of death, an alternative may be suitable when traditional autopsy by a perinatal pathologist is not available or declined. Methods: Among 3137 cases evaluated through the Wisconsin Stillbirth Service Program (WiSSP), a community‐based program for etiologic evaluation of second trimester miscarriage, stillbirth, and early neonatal death, most diagnoses are based on multiple types of data including placental pathology, clinical examination, photographs, maternal records, radiographs, and laboratory testing. Results: Cases in the WiSSP cohort without autopsy have nearly the same overall rate of diagnosis as those with traditional autopsy (56% vs. 58%). Review of the literature shows that although recent systematic protocols including autopsy, placental pathology and genetic studies yield a definite or probable diagnosis in 70% or more, both healthcare providers and families desire less invasive options. Several minimally invasive protocols substituting imaging, primarily MRI, for traditional autopsy have been proposed, but the numbers of deaths evaluated are still very small. Conclusion: We join others who have promoted the benefits of a targeted or less invasive protocol to study perinatal deaths, and emphasize integration of clinical data, selective imaging, genetic testing, and parental counseling. Birth Defects Research 109:1430–1441, 2017.© 2017 Wiley Periodicals, Inc.